Testing the Origins of the Family Patrimony in Everyday Law - Kasirer, Nicholas (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1995)
This essay seeks to reevaluate the origins of the family patrimony by challenging the idea that the provisions introduced into the Civil Code of Québec in 1989 amounted to new law. The family patrimony is not simply a statutory trust borrowed maladroitly from Ontario, nor does it reflect a moral postulate that, prior to 1989, had no legal status. It may be argued, in advance of sociological study, that the family patrimony should be understood as reflecting customary norms that were already present in the Quebec legal order at the time of its enactment. Where wealth is accumulated by the spouses during the period that marriage is lived as a joint economic endeavour, rules of everyday law may require the sharing of certain property without regard to which of them has formal title thereto. These customary norms, obscured doctrinally by a modern disinclination among jurists to look beyond state-made law and its adjuncts in the regulation of married life, are potent sources of family property law. Once the manner in which everyday law complements the formal law of matrimonial property is made plain, it becomes apparent that the claim to a share of the family patrimony is not, in fact, a break with tradition in Quebec's Civil law of family property.